THE ROLE OF PAI TEACHERS AS MOTIVATORS IN ONLINE LEARNING DURING THE PANDEMIC - Rahman, Lestari Aulia; Permana, Hinggil (Universitas Islam Madura, 2025)
This research aims to explore the transformative role of Islamic education in strengthening religious moderation in contemporary society. This study adopts a qualitative descriptive approach by analyzing the perceptions of Islamic education practitioners, religious leaders, and community stakeholders regarding the integration of moderation values into the teaching and learning process. Data was obtained through in-depth interviews, focus group discussions, and document analysis, which were then validated using triangulation techniques to ensure credibility. These findings reveal that Islamic education contributes significantly to shaping moderate attitudes among students and society by emphasizing the values of inclusiveness, tolerance, and balance in religious understanding. In the context of a digital society, Islamic education is not only challenged to provide a counter-narrative to intolerance and extremism disseminated through social media, but also to develop critical thinking skills and digital literacy that empower students to navigate online information responsibly. Furthermore, this study highlights the importance of curriculum innovation, teacher capacity building, and community-based collaboration in encouraging sustainable moderation practices. This study concludes that Islamic education can be a strategic medium to promote religious moderation, social cohesion, and resilience to ideological polarization. These findings offer theoretical insights and practical implications for policymakers, educators, and scholars in designing values-based education frameworks that align with the global peace and sustainability agenda.